PENGARUH KOMITMEN ORGANISASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Rolindo, Ricky Hasiholan; Sudiro, Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The Covid-19 pandemic that had occurred from 2020 to 2022 in Indonesia adversely affected multiple sectors of industry; one of which is tourism and hotel. Savana, a hotel in Malang city that was also affected by the outbreak, responded to the unwanted condition by temporarily laying off some of their employees. This policy, however, is considered as a threat for job security, and it affects employees’ organizational commitment and work motivation, leading to lower performance. The goal of this study is to measure the influence of organizational commitment and work motivation on employee performance. The sample of this quantitative explanatory research is 75 employees of the hotel that was affected by the temporary layoff. The data was acquired from questionnaires, that have been tested for validity and reliability. The results of the analysis suggest that organizational commitment and work motivation simultaneously have a significant impact on performance by 14.6% with the F statistics of 7.317 > the T table of 3.12 and the coefficient of determination of 0.146 at the significance level of 0.001. further, organizational commitment has no significant effect on employee performance with the t statistics of 1.291 < t table of 1.993 at sig. of 0.201, while work motivation significantly influences employee performance at the t statistics of 2,847 > t table of 1,993 at sig. of 0.006.